2021
DOI: 10.1002/ajmg.a.62257
|View full text |Cite
|
Sign up to set email alerts
|

A family with partially penetrant multicentric carpotarsal osteolysis due to gonadal mosaicism: First reported case

Abstract: Multicentric carpotarsal osteolysis (MCTO) is an autosomal dominant condition characterized by carpal-tarsal abnormalities; over half of affected individuals also develop renal disease. MCTO is caused by mutations of MAFB; however, there is no clear phenotype-genotype correlation. We describe the first reported family of variable MCTO phenotype due to mosaicism: the proband had classical skeletal features and renal involvement due to focal segmental glomerulosclerosis (FSGS), and the father had profound renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Most of them resembled JIA; however, treatment could not prevent disease progression and bone loss. 2,[4][5][6][7][8][9][10][11][12][14][15][16][17][18] Similarly, although pain did improve with anti-tumor necrosis factor medications in our patient, osteolysis could not be avoided. The main problem in MCTO was suggested to be increased RANKL activation and excessive osteoclastic activity, but the cause of the selection of distinctive bones remains unclear.…”
Section: Discussionmentioning
confidence: 87%
“…Most of them resembled JIA; however, treatment could not prevent disease progression and bone loss. 2,[4][5][6][7][8][9][10][11][12][14][15][16][17][18] Similarly, although pain did improve with anti-tumor necrosis factor medications in our patient, osteolysis could not be avoided. The main problem in MCTO was suggested to be increased RANKL activation and excessive osteoclastic activity, but the cause of the selection of distinctive bones remains unclear.…”
Section: Discussionmentioning
confidence: 87%
“…A total of 18 (3 novel) disease-causing variants in MAFB gene were identified and were classified according to the American College of Medical Genetics and Genomics (ACGM) classification (see Supplementary Material Table S1 and Figure S1 ). All subjects carried missense variants in heterozygous state and all variants lie within a short region of amino-terminal transcriptional activation domain (amino acids 54–71) [ 1 ], one subject presented somatic mosaicism [ 2 ]. Genetic testing of parents was available in 22 cases: 60% (13/22) resulted sporadic cases (i.e., de novo mutations), 40% (9/22) resulted inherited mutations.…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, Zankl et al [ 1 ] for the first time identified missense mutations clustering within a 51 base pair region of the single exon of MAFB in five unrelated simplex cases of MCTO. After that, 57 cases with genetic diagnosis were reported in the literature [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. All cases showed a large phenotypical heterogeneity, even among patients presenting the same variant [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms responsible for osteoclast disease as a result of the MAFB mutation are unknown. MCTO cases are reportedly complicated by hereditary FSGS, which is characterized by podocyte injury (31)(32)(33). To analyze the pathogenesis of this syndrome, we used CRISPR/Cas9 genome editing to create homozygous mice harboring the MCTO mutation.…”
Section: Mafb Mutations In Human Diseasementioning
confidence: 99%